Guidelines for the Identification of the Mandibular Vital Structures: Practical Clinical Applications of Anatomy and Radiological Examination Methods - Hom-Lay Wang; Gintaras Juodzbalys (eJournal of Oral Maxillofacial Research, 2010)
Objectives: The purpose of this article was to review the current available clinical techniques and to recommend the most appropriate imaging modalities for the identification of mandibular vital structures when planning for oral implants.Material and Methods: The literature was selected through a search of PubMed, Embase and Cochrane electronic databases. The keywords used for search were mandibular canal, mandibular incisive canal, mental foramen, anterior loop of the mental nerve, radiography, dental implants. The search was restricted to English language articles, published from January 1976 to January 2010.Results: In total 111 literature sources were obtained and reviewed. The peculiarities of the clinical anatomy of mandibular canal, mandibular incisive canal, mental foramen and anterior loop of mental nerve were discussed. Radiological diagnostic methods currently available for the identification of the mandibular vital structures when planning for oral implants were presented. Guidelines for the identification of the mandibular vital structures in dental implantology were made.Conclusions: The proposed guideline provides clinicians a tool in proper identifying the important mandibular vital structures thus minimizing the potential complications during implant surgery.